Serendipity : suite for Chinese orchestra No.1 - Jahnichen, Gisa (Universiti Putra Malaysia Press, 2012)
The pieces created from these ideas for the UPM gamelan set reflect typical principles of gamelan conditions such as a regular cyclic construction of musical sections, non semitone melodies, non accidental scales, narrow range and a strong focus on metro-rhytmic versatility as one of the few tools in shaping individuality. The Suite “translates” the gamelan ideas into the language of a Chinese Orchestra. The six pieces chosen apply harmonic progressions, open up the range limitation and in some parts the regular shape of gamelan pieces. However, the melodic ideas of the pieces still remain as well as the continous metric pulsation with its essential rtythmic components. Thus, the suite is grown from the ground of musical possibilities in Malaysia and still on the way to become an exciting material of departure to new dimensions of creativity.